Organisational Culture and Environmental Performance of Hospitality Firms in South Africa - FATOKI, Olawale (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
The purpose of the study is to investigate the impact of organisational culture on firm environmental performance in the context of the hospitality sector. The study used the quantitative research approach with descriptive and causal research design. The Denison organisational culture questionnaire was used to measure organisational culture. The Denison questionnaire contains four traits namely involvement, consistency, adaptability and mission. The questionnaire was distributed among 500 owner/managers of formal hotels and guest accommodations in South Africa. Data gathered were analysed using descriptive statistics and structural equation modelling. The results of the study indicate that the four traits of organisational culture (involvement, consistency, adaptability and mission) have significant positive impacts on the environmental performance of firms in the hospitality sector. The findings of the study can assist firms in the hospitality sector to understand the significance of internal intangible factors such as the organisational culture in the implementation of environmental sustainability initiatives.